Response and resilience of karst subterranean estuary communities to precipitation impacts - Fernando Calderón Gutiérrez; Thomas M. Iliffe; Elizabeth Borda; Germán Yáñez Mendoza; Jessica Labonté (Ecology and Evolution, 2023)
Abstract The impact of meteorological phenomena on ecosystem communities of karst subterranean estuaries (KSEs) remains unknown. KSEs are characterized by vertically stratified groundwater separated by a halocline and host endemic aquatic cave‐adapted fauna (stygobionts). In October 2015, 8 days of heavy precipitation caused the first recorded mortality event in the KSE. This event was marked by a halocline shift 5 m deeper. The present study aimed to provide insights into resilience of KSEs faunal communities to temporal shifts in temperature and precipitation. Cave water temperature decreased on average 0.0068°C per mm of accumulated precipitation over 4 days, which can add up to, and surpass, the interannual temperature variation in cases of heavy precipitations. Biological surveys (2012–2021) conducted within cave systems El Aerolito and La Quebrada, in Cozumel, indicated that change in community structure was not detected and stygobionts were resilient; however, marine species inhabiting the caves were impacted. Overall, the faunal community at KSEs remains resilient within short‐term meteorological phenomena despite shifts of non‐stygobionts.